Standing behaviour of non-ambulant children and youth using powered wheelchair standing devices (PWSDs): an interrupted time series pilot study. - Field, Debra A.; Borisoff, Jaimie; Chan, Franco H. N.; Livingstone, Roslyn W.; Miller, William C. (Disability & Rehabilitation: Assistive Technology, 2025)
This study investigated "What is the standing behaviour for children and youth with substantial motor impairment due to a neuromotor disorder and does it change over the first three months of use after introducing a powered wheelchair standing device (PWSD) intervention?" As part of a larger interrupted time series with five timepoints, dataloggers measured PWSD seat angle range, frequency and duration for five days, at one-week, one-month and three-months post-PWSD provision with a purposefully-selected sample. Two males and four females aged 7-18 years with diagnoses of spina bifida or cerebral palsy participated; all had minimal experience standing and walking. PWSD seat angle movement relative to horizontal (typical wheelchair seat orientation) was categorised as sitting ≤ 30 degrees (°), weightbearing 31°-60°, and standing > 60°. Descriptive statistics and visual analysis described sample and recordings. Standing behaviours, individualised across participants, varied across timepoints. Total frequency (number of events over 5 days) ranged from 0-13 times in weightbearing and 0-12 times in standing. The two youngest stood more frequently. Duration (minutes) ranged from 0.4-71.5 for weightbearing and 0.4-80.2 for standing; most lasted <3 min. Although PWSDs hold potential for increasing standing behaviour, contextual factors strongly influenced use. Findings reinforce the importance of considering children's and youth's participation goals and how those may affect weightbearing or standing behaviour. For those considered non-ambulatory since birth, additional instruction and support is needed to optimise use of PWSD standing functions for independent body position changes as they engage in functional activities and fully integrate PWSD use into daily life. IMPLICATIONS FOR REHABILITATION: For non-ambulant children and youth with substantial chronic motor impairments, PWSDs have the potential for promoting independent weightbearing and standing, enabling one's own control over body positioning in daily life. Data logger technology offers important objective information about children's and youth's PWSD use. When implementing PWSD interventions, a multitude of personal and environmental factors can influence weightbearing and standing behaviour, including engagement in meaningful life activities such as self-care, play, learning and social interaction. Children and youth who have little to no experience standing or moving about in an upright standing posture independently may benefit from specific training and ongoing therapy support to optimise PWSD use utilising a variety of body posture orientations to promote participation in daily life with family and friends.